Analisis Pengaruh Manajemen Mutu Terhadap Kinerja, Efektivitas, dan Keandalan pada Transportasi Kereta Rel Listrik (KRL) - Asha Ayu Valmaida; Aulia Rofika Dewi; Dian Panca Rachmawati; Raisya Kanahaya Achmad; Yoseva Ilona Viska (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Public transportation plays a significant role in supporting urban mobility. One of the widely used modes of public transportation is Electric Train (Kereta Rel Listrik or KRL), a railway system powered by electricity and operates on separate tracks from road traffic. This research aims to analyze the influence of quality management on the performance, effectiveness, and reliability of KRL services. The method used is qualitative methodology and survey, by analyzing and describing the phenomena or research objects through the observation of survey results conducted on users of the KRL Commuter Line Jabodetabek service. The results show that public transportation not only serves to transport passengers but also must provide safe and comfortable services to continue to be favored by the public. The satisfaction of KRL users greatly depends on the quality of service provided.